Study of spirocarbon and its derivatives as growth controlling agents in plants (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The article elucidates possibility of obtaining spirocompounds by condensation of carbonyl compounds with carbamides and growth regulating activity of derivatives.
Keywords: spirocompounds, spirocarbon, condensation, growth controlling activity, seedlings of tomato and wheat.